Road safety strategic analysis in Brazil: indicator and index research - Bastos, Jorge Tiago (2014)
The intense economic growth that Brazil has experienced in recent decades and its consequent explosive motorization process have resulted in an undesirable impact: the continuously increasing trend in traffic fatality numbers. This study presents a research on indicators and indexes with the objective of delivering both overall and disaggregated evidence about the road safety performance and targets in fatality reduction in Brazil at the state level taking the exposure into account. The intention is to support road safety strategic analysis in the country and to contribute to improve this critical scene. The methodological structure of this thesis consists of the following three main parts: (I) diagnosing the road safety situation at the state level using final outcome related information, in particular traffic fatality risk data; (II) setting a target number of traffic fatalities based on the relationship between the exposure level and the number of traffic fatalities in each state; and (III) suggesting domains for improvements based on the research of safety performance indicators representing three domains (road user, environment and vehicle) throughout the states. From a benchmarking point of view, we divided the Brazilian states into three separate clusters in order to provide more realistic state performance comparisons. After a data collection and indicators selection step, Data Envelopment Analysis (DEA) was the method used for executing the different steps, with the application of four different types of models specially developed for the identified research purposes. In addition, by means of bootstrapping the DEA scores we measured the sensitivity of the results to possible variations in the input data, for example concerning data quality and availability. As a result, we provided a road safety diagnosis per state as well as traffic fatality targets according to different perspectives: the entire group of road users (motorized and nonmotorized ones), motor vehicle occupants, and finally a disaggregated performance evaluation by running four separate DEA models (for motorcycle, car, truck and bus). Moreover, the SPI research including a hierarchy of 27 safety performance indicators expressed the states relative performance on the main road safety domains. Lastly, state profiles compiling all this information summarized the \"per state\" findings.